Оцінка соціально-економічної ситуації на основі аналізу статистичних показників (на прикладі України) - Гармаш, Сергій Володимирович (НТУ "ХПІ", 2013)
У статті робиться оцінка соціально-економічної ситуації, яка склалася в Україні, на основі аналізу міжнародних рейтингів та індексів; просліджується процес у динаміці, виявляється взаємозв’язок та взаємообумовленість різноманітних чинників; надаються рекомендації щодо шляхів розвитку на перспективу в умовах системної кризи. Особлива увага приділяється моральному виміру усіх учасників процесу.

The estimating of social and economical situation in Ukraine on the base of the analysis of the international ratings and indexes is made in the article. Tracing the process in action, finding out of interaction and interconditionality of different factors are also made. Some recommendations according to the ways of the development in the nearest future under conditions of the systemic crisis are proposed. Great attention is paid to the moral estimation of the all participants of the process.
Keywords: рейтинги міжнародні; індекси міжнародні; криза системна; вимір моральний; social situation; economical situation; international ratings; international indexes; systemic crisis; moral estimation